Impact of xenon doping in the scintillation light in a large liquid-argon TPC. Issue 1 (1st November 2022) - Soto-Oton, J.; ,
Abstract : The use of xenon-doped liquid argon (Xe-doped LAr) is a promising alternative for large-scale liquid argon Time Projection Chambers (LAr-TPC), since it mitigates the light suppression due to impurities and it also improves the photon-detection efficiency and uniformity with the distance. This study analyses the impact of using Xe-doped LAr in ProtoDUNE Dual-Phase, a 750 ton Dual-Phase LAr-TPC placed at CERN. ProtoDUNE Dual-Phase completed a Xe-doping data-taking campaign in summer 2020 by re-filling the detector with 230 tons of Xe-doped LAr contaminated with nitrogen, and performing dedicated nitrogen injections. The effects of the presence of Xe at 5.8 ppm in the scintillation light production and propagation are analysed in this paper, showing an increase of the collected photons, but a suppression of the light signal amplitude. A 60% increase of the light attenuation length is measured. The impact on the scintillation time profile is also studied. A model to fit the time profile is proposed and the time constants of the physics processes are obtained.